2014
DOI: 10.1063/1.4871475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of voltage polarity on oxidation-reduction potential by plasma in water

Abstract: Use of plasma in water for water treatment and medical treatment is growing and raises expectations of finding advanced functions such as an increase of biological compatibility. In the present study with a focus on the variation of oxidation-reduction potential (ORP), relationships between the electrode polarities of plasma in water and the change of water quality such as conductivity, H2O2 concentration, dissolved hydrogen concentration, pH and ORP were revealed. Similar line spectra of radiation at the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Discharge with water as a cathode is usually much more efficient for H 2 O 2 production as is seen from Fig. 4 and reported in many researches [30,31]. When liquid acts as an anode, the cathode voltage fall is formed on the metallic electrode, and the charged particles are electrons entering the anodic solution [25].…”
Section: Effect Of the Discharge Current Of Peroxide Formationmentioning
confidence: 84%
“…Discharge with water as a cathode is usually much more efficient for H 2 O 2 production as is seen from Fig. 4 and reported in many researches [30,31]. When liquid acts as an anode, the cathode voltage fall is formed on the metallic electrode, and the charged particles are electrons entering the anodic solution [25].…”
Section: Effect Of the Discharge Current Of Peroxide Formationmentioning
confidence: 84%
“…In‐liquid plasma technologies can be categorized into two types, based on the electrode configuration. In the first type, both electrodes are submerged in the liquid . Submerged electrode type discharge requires bubble generation for plasma ignition.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma generated in the liquid phase, i. e., in-liquid plasma, has great potential for a wide range of applications, such as water purification [1][2][3][4][5] and material synthesis. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Low-cost, high-quality materials have increasingly become more important for solving environmental concerns with clean water, energy production, [20][21][22][23][24] and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akishev et al studied the development of a plasma sheet structure in a surface dielectric barrier discharge powered with a single long pulse of negative polarity, and showed the effect of pulse amplitude and duration on the development of streamers and leaders in Ar gas at atmospheric pressure [29]. Miyahara et al reported that positive streamers were stronger and longer than those of negative polarity; they also showed that the concentration of H 2 O 2 was increased with positive polarity of the applied voltage [30]. Previous studies showed effects of voltage amplitude applied directly in water on both the discharge processes and treatment of polluted water [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%